Analisis Respon Siswa Terhadap Proses Pembelajaran Berbantuan Multimedia Interaktif di Sekolah Dasar - Rieke Alyusfitri; Yulfia Nora; Habib Ibnu Fadhillah (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
Along with the challenges of an increasingly complex era of development, the demand for quality teaching continues to rise, which affects the meaning and purpose of teaching and education. Good teaching is based on the teacher's ability to teach as well as the environment that supports the teacher to teach, including the pupils and the learning media used. Teachers are required to innovate in learning by providing innovative, inspiring, entertaining and technology-based learning media. Interactive multimedia is an alternative medium that supports active student learning and increases participation in the learning process This study analyzes how students respond to learning in elementary schools by using interactive multimedia. The sample of this study consisted of 64 elementary school students from three elementary schools in Padang City. The instrument of this study used data from student response questionnaires. Data were analyzed using descriptive analysis techniques to find answers to the questions identified in the study. Research results show that 86.80% of students have a very positive attitude towards using interactive multimedia for learning because learning activities conducted through interactive multimedia are more active and students enjoy it. From this, it can be concluded that student reactions to learning supported by interactive multimedia in elementary schools are very positive.